NUMERICAL MODELING OF THE RIVER POLLUTION - Biliaiev, M. M.; Pokutneva, L. V. (Science and Transport Progress, 2009)
The 2D numerical model to simulate the pollutant dispersion in rivers is offered. The model is based on the equation of potential flow and the transport model. The results of numerical experiment are presented.